Efektivitas Pengendalian Internal Berbasis COSO dalam Pencegahan Fraud pada Pengelolaan Kas: Studi Literatur dengan Identifikasi Faktor Dominan - Ramadanis Ramadanis; Olivia Rahmadani; Doni Septian; Alina Tasya; Salwa Agusti Putri; Nayla Atissha Wulandari; Andrea Khalistio Safitri (INDO PUBLISHING, 2026)
This study aims to analyze the effectiveness of internal control based on the COSO framework as an effort to prevent fraud in cash management and identify the dominant factors that influence its effectiveness. The study uses a qualitative approach with a literature study method through a review of various scientific articles, books, reports, and relevant references published in the 2020–2025 period. Data collection was carried out through a literature review, then analyzed through the stages of identification, selection, extraction, grouping based on two main themes (effectiveness and factors), and synthesis of research findings to produce a conceptual framework. The results of the study indicate that internal control plays a significant role in minimizing the risk of fraud in cash management. The implementation of effective internal controls, such as segregation of duties, authorization systems, transaction documentation, monitoring, and periodic reconciliation, can reduce the opportunity for fraud. This answers the first problem formulation regarding the effectiveness of internal control. However, the effectiveness of internal control is not only determined by formal procedures, but is also influenced by six main factors: the quality of human resources, leadership integrity, segregation of duties, organizational culture, utilization of information technology, and ongoing supervision. Of these six factors, human resource quality and leadership integrity were identified as the most dominant factors that consistently influence the effectiveness of internal control, addressing the second research question. Research findings indicate that weaknesses in these factors can open up opportunities for fraud, even when a control system is in place. Therefore, organizations need to consistently integrate all COSO components and strengthen ethical values ​​and HR competencies to enhance fraud prevention and safeguard organizational assets.